Design of a subnonsecond Gauusisan pulse generator based on the RF transistor - YANG Feng1; XUE Quan2; CHAN Chi-hao2 (Tongxin xuebao)
A simple and low cost subnonsecond Gaussian pulse generator was developed using RF transistor,chip resistors,and chip capacitors.The generator utilized a differential circuit to convert signal from the FPGA into a pairs of positive and negative pulses,which was then used to control the “on” and “off” states of the RF transistor,thus generating an ultra-short pulse through the charging and discharging of the capacitor.The measured results shows that output waveform have 0.8ns pulse duration and morn than 1.8V from an input wave of 25MHz repetition rate.Good agreement between the measured and calculated results is achieved.This circuits is suitable for microwave integrated circuits（MIC）.